In vitro Antileishmanial, Antitrypanosomal, and Anti-inflammatory-like Activity of Terminalia mollis Root Bark - Muganga, Raymond; Bero, Joanne; Quetin-Leclercq, Joëlle; Angenot, Luc; Tits, Monique; Mouithys-Mickalad, Ange; Franck, Thierry; Frédérich, Michel (Planta Medica, 2020)
This study aims at determining the in vitro antitrypanosomal, antileishmanial, antioxidant, and anti-inflammatory-like activities of Terminalia mollis root crude extracts. The antitrypanosomal and antileishmanial activities on Trypanosoma brucei brucei (strain 427) and promastigotes of Leishmania mexicana mexicana (MHOM/BZ/84/BEL46) were evaluated in vitro. The methanolic root bark extract and standards were profiled by HPLC-PDA, and the majority of compounds identified using literature data. The in vitro antioxidant and anti-inflammatory-like activities were determined by evaluating the effect of crude extracts on reactive oxygen species produced by phorbol 12-myristate 13-acetate-stimulated equine neutrophils using lucigenin-enhanced chemiluminescence and on purified equine myeloperoxidase activity measured by specific immunological extraction followed by enzymatic detection. The methanolic, aqueous crude extract, and aqueous crude extract free of tannins exhibited good growth inhibition on Trypanosoma brucei brucei (IC50 3.72, 6.05, and 4.45 µg/mL respectively) but were inactive against Leishmania mexicana mexicana (IC50 > 100 µg/mL). Suramin (IC50 0.11 µg/mL) and amphotericin (IC50 0.11 µg/mL) were used as standard respectively for the antitrypanosomal and antileishmanial activity. Very interesting antioxidant and anti-inflammatory-like activities were observed with 50% hydroethanolic, aqueous crude extracts, and aqueous crude extract free of tannins as well as with pure punicalagin, gallic, and ellagic acid (IC50 0.38 – 10.51 µg/mL for 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid), chemiluminescence, and specific immunological extraction followed by enzymatic detection assays. The study results support traditional medicinal use of the plant for the treatment of parasitical disorders and revealed for the first time the antitrypanosomal potential, anti-inflammatory-like, and antioxidant activity of Terminalia mollis root.
Keywords: Terminalia mollis; antitrypanosomal; antileishmanial; antioxidant; anti-inflammatory-like activity; Combretaceae